Analisis Kelayakan Industri Rumah Tangga Keripik Singkong di Desa Kasarangan Kecamatan Labuan Amas Utara - Rum Van Royensyah; Sundariah Sundariah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2014)
Integrated processing of cassava in the household scale cassava chips industry is an effort to optimize each stage of cassava processing and the utilization of by-products arising from the industry to increase the added value of cassava. Cassava is one of the commodities that are often found in rural areas such as in Kasarangan Village, this study aims to determine the size (i) of production costs (ii) revenue (iii) benefits and (iv) business feasibility of cassava chips household business in Kasarangan Village, Labuan Amas District, North, Hulu Sungai Tengah Regency. The results of this study indicate that the business of home industries of cassava chips that were cultivated by entrepreneurs / respondents in this study, the average total cost reached Rp. 22,820,286.00. Average fixed costs reach Rp. 2,228,649.00 / month and the average variable cost reaches Rp. 20,591,636.00 / month. The average revenue is Rp. 54,000,000.00 / month, with an average profit reaching Rp. 31,179,714.00 / month. Based on the data presented, the cassava chips household industry in Kasarangan Village, Labuan Amas District, Hulu Sungai Tengah Regency. With the average RCR value of the business reaching 2.37, it is worth trying